1998
DOI: 10.1149/1.1838359
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Cathodic Electrodeposition of Zinc Oxide and Zinc Hydroxychloride Films from Oxygenated Aqueous Zinc Chloride Solutions

Abstract: Films of zinc oxide and related compounds [ZnO, ZnO(OH)5, Zn(OH)Cl9] are electrodeposited cathodically in aqueous zinc chloride solutions using dissolved oxygen as a precursor. The influence of the precursor concentrations, pH, and deposition temperature on the growth, composition, and properties of the films are investigated by means of in situ techniques: voltammetry electrochemical quartz-crystal microgravimetr surface pH, and ex situ techniques: X-ray diffraction, infrared spectroscopy, scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
456
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 604 publications
(473 citation statements)
references
References 11 publications
16
456
0
1
Order By: Relevance
“…5 Qualitative comparisons of relative peak heights ( Figure 1) also confirmed that, while our samples are polycrystalline, there is a preferred (002) orientation in the deposit, which is typical for electrodeposited ZnO. 4,15,22 This (002) texture is moderately accentuated for samples deposited at -1.1 V (pH 6.5), coinciding with a morphological change from hexagonal crystallites to rice-like structures, as shown in Figure 2, and reported previously. Despite the fact that XRD shows no obvious structural differences among samples prepared over this potential (-0.9 V to -1.3 V) and pH range (pH 4-7), we find drastically different carrier Since carrier concentration changes can influence optical as well as electronic properties, we also compared trends in optical absorption edges, obtained from diffuse reflectance spectra, with electrodeposition conditions.…”
Section: Resultssupporting
confidence: 88%
“…5 Qualitative comparisons of relative peak heights ( Figure 1) also confirmed that, while our samples are polycrystalline, there is a preferred (002) orientation in the deposit, which is typical for electrodeposited ZnO. 4,15,22 This (002) texture is moderately accentuated for samples deposited at -1.1 V (pH 6.5), coinciding with a morphological change from hexagonal crystallites to rice-like structures, as shown in Figure 2, and reported previously. Despite the fact that XRD shows no obvious structural differences among samples prepared over this potential (-0.9 V to -1.3 V) and pH range (pH 4-7), we find drastically different carrier Since carrier concentration changes can influence optical as well as electronic properties, we also compared trends in optical absorption edges, obtained from diffuse reflectance spectra, with electrodeposition conditions.…”
Section: Resultssupporting
confidence: 88%
“…16 Relative peak intensity data show that our films are truly polycrystalline but with a preference for ͑001͒ orientation, as is typical for electrodeposited ZnO. 4,14,20 Optical absorption edge values for these same ZnO films, calculated from diffuse reflectance measurements, lie in the accepted range for native ZnO ͑3.3± 0.1 eV͒. 9,11 The rectifying behavior of our electrodeposited junctions compare favorably with ZnO-based Schottky junctions prepared by other methods, with forward-current to leakagecurrent ratios of ϳ50: 1 and no breakdown at reverse-bias voltages up to 2 V. It is customary to compare the rectifying behavior with an ideal Schottky response as outlined below:…”
mentioning
confidence: 80%
“…Similar results are observed when depicting the electrochemical results except for 0 days because of the immediateness of the electrochemical measurement. Although, the trials in real time give lower corrosion rates values than those obtained through electrochemical methods [3,11] . Moreover, the potential of the Zn/Zn 2+ reaction determined from the solubility…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the application of the Stern-Geary approximation should not be employed as it has been concluded that the difference between the corrosion potential and the reversible potential should be more than 13 mV [11,17] . Nevertheless, only slight differences are found when comparing the two methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation